2021
DOI: 10.3390/pathogens10050598
|View full text |Cite
|
Sign up to set email alerts
|

Biocidal Resistance in Clinically Relevant Microbial Species: A Major Public Health Risk

Abstract: Antimicrobial resistance is one of the greatest dangers to public health of the 21st century, threatening the treatment and prevention of infectious diseases globally. Disinfection, the elimination of microbial species via the application of biocidal chemicals, is essential to control infectious diseases and safeguard animal and human health. In an era of antimicrobial resistance and emerging disease, the effective application of biocidal control measures is vital to protect public health. The COVID-19 pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 94 publications
0
48
0
Order By: Relevance
“…Whilst offering alternative therapeutics is one way of dealing with rising antibiotic resistance, a more useful method to combat the issue is working towards infection prevention. Effective biocidal options play a crucial role in reducing drug-resistant bacteria and their biofilm counterparts that persist on clinical surfaces and the surrounding environment, where the current emergence of biocide-resistant bacterial strains have made it even more difficult to eliminate them [ 6 ]. In the present study, all biocidal agents, including peracetic acid, triameen and BAC demonstrated excellent activity against MDR GNB at concentrations recommended by the manufacturer (0.1%) ( Table 4 and Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst offering alternative therapeutics is one way of dealing with rising antibiotic resistance, a more useful method to combat the issue is working towards infection prevention. Effective biocidal options play a crucial role in reducing drug-resistant bacteria and their biofilm counterparts that persist on clinical surfaces and the surrounding environment, where the current emergence of biocide-resistant bacterial strains have made it even more difficult to eliminate them [ 6 ]. In the present study, all biocidal agents, including peracetic acid, triameen and BAC demonstrated excellent activity against MDR GNB at concentrations recommended by the manufacturer (0.1%) ( Table 4 and Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies report a prevalence of 8% of hospitalised patients developing HAIs, with 20% of these involving MDR species having a higher risk of mortality or re-admission [ 4 ] The European Centre for Disease Prevention and Control (ECDC) estimates approximately 8.9 million HAIs yearly in Europe, with the Gram-negative Pseudomonas aeruginosa and the Enterobacterale Escherichia coli prominent agents of disease [ 5 ]. Importantly, Gram-negative non-fermenting species such as P. aeruginosa are intrinsically resistant to common antibiotics such as ampicillin, cephalosporins, and macrolides, where MDR is common [ 6 ]. The extended-spectrum β-lactamase enzymes (CTX-M, TEM, SHV, PER, VEB, and TLA) which hydrolyse extended-spectrum cephalosporins and penicillins are abundant in GNB and are plasmid transferrable, promoting pan-resistance in species [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, chlorine compounds can react with a vast range of organic and inorganic materials and other anthropogenic chemicals. This leads to the formation of DBPs in different types of aquatic systems like wastewater, surface water, and tap water due to elevated CBD application (Li et al 2021 ; Meade et al 2021 ; Paul et al 2021 ; Wang et al 2021 ).…”
Section: Fate and Transport Of Cbd S During And After Applicationmentioning
confidence: 99%
“…The biodiversity of microbial communities is maintained by the counteraction of the production and degradation of antibiotics [1]. The external influence of disinfectants and antibiotics drives additional selective pressures, dramatically reducing the biodiversity of microbiomes [2,3] and providing conditions for antibiotic resistance propagation [4] and evolution [5]. Reduced microbiome biodiversity, in turn, is attributed to its impaired functionality [6,7] and health disorders [8], including the emergence and transmission of infectious diseases [9], autoimmune diseases [10,11], and allergic diseases [12,13].…”
Section: Introductionmentioning
confidence: 99%